Transpapillary biliary biopsy for malignant biliary strictures: comparison between cholangiocarcinoma and pancreatic cancer. Issue 1 (December 2016) - Chen, Wei-Ming; Wei, Kuo-Liang; Chen, Yi-Shing; Chang, Pey-Jium; Tung, Shui-Yi; Chang, Te-Sheng; Huang, Hao-Chun; Shen, Chein-Heng; Hsieh, Yung-Yu; Wu, Cheng-Shyong
Abstract Background Tissue sampling for biliary stricture is important for differential diagnosis and further treatment. This study aims to assess the differences of transpapillary biliary biopsy for malignant biliary strictures between cholangiocarcinoma and pancreatic cancer. Methods From January 2010 to December 2013, we retrospectively studied 79 patients who suffered from biliary strictures and received transpapillary forceps biopsy after sphincterotomy for tissue sampling. The diagnostic sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of forceps biopsy were calculated in all cases for both cholangiocarcinoma and pancreatic cancer patients. Possible factors that distinguish malignant strictures from benign strictures and which could affect the accuracy of tissue sampling were analyzed. Results There are 65 malignant and 14 benign biliary stricture patients enrolled. The malignant group has a significantly higher serum bilirubin level than the benign group, but age, clinical presentation, level of serum carcinoembryonic antigen (CEA), carbohydrate antigen (CA) 19-9, and alkaline phosphatase are not. The sensitivity, specificity, PPV, and NPV of forceps biopsy for biliary stricture are 53.85, 100, 100, and 31.82 %, respectively. The cholangiocarcinoma group has a higher sensitivity (73.53 versus 29.17 %, p < 0.001), older age, lower CA 19-9 level, and more common hepatic duct strictures than the pancreatic group. The age, serum CEA, CA 19-9 and the alkaline phosphatase level, serum bilirubin level >10 mg/dL, tissue sampling ≧3 are not significant factors affecting diagnostic accuracy in forceps biopsy for pancreatobiliary strictures. There is neither major bleeding nor perforation in our study. Conclusions Transpapillary forceps biopsy of biliary strictures after sphincterotomy for tissue sampling is safe and a significantly higher sensitive method in cholangiocarcinoma but not in pancreatic cancer.